Mallarmé's sunset poetry at the end of time - Norman, Barnaby (Legenda, 2014)
"The writings of the great Symbolist poet Stéphane Mallarmé (1842-1898) were to become uniquely influential in twentieth century literary criticism. For critics and philosophers such as Maurice Blanchot and Jacques Derrida, Mallarmé's name came to represent a rupture in literary history, and an opening of literature onto a radically new kind of writing. Through close readings of key works, Norman retraces Mallarmé's trajectory as a poet, showing in particular how he positioned his work in relation to Hegel's Aesthetics. Analysing the motif of the sunset Norman argues that Mallarmé situated his work at the conclusion of the history of art, in Hegelian terms, and it is this that made him so interesting for Blanchot and Derrida. Their readings, born of their wish to subvert Hegel's totalizing impulse, give rise to an entirely new view of works now almost universally seen as masterpieces."--P. [4] of cover
Includes bibliographical references and index
Keywords: Mallarmé, Stéphane / 1842-1898 / Criticism and interpretation; Hegel, Georg Wilhelm Friedrich / 1770-1831 / Ästhetik; Hegel, Georg Wilhelm Friedrich -- 1770-1831; Mallarmé, Stéphane -- 1842-1898; Twilight in literature; Metaphor in literature; Symbolism (Literary movement) / France; Untergang -- Astronomie, Motiv; Rezeption; Ästhetik; Sonne -- Motiv; Symbolismus; Sun / In literature; Sun / Rising and setting; Frankreich